Effect of sealed water curing and fiber length on compressive strength and fracture energy of fly ash-based geopolymer mortars - Adil Gültekin (Journal of Sustainable Construction Materials and Technologies)
n this study, the effect of the curing method and polyvinyl alcohol (PVA) fiber inclusion on some engineering properties of fly ash-based geopolymer mortars was examined. In this context, six fly ash-based mortars were produced using sodium hydroxide and sodium silicate solution. The fracture energy values were determined with notched samples of 50×50×240mm dimensions, and a clip-on gage was used to measure the crack mouth opening displacements. The notch width and notch height were 3 mm and 10 mm, respectively. Specimens were cured in hot water (80 °C) for 18 hours. Before curing, one series of samples was sealed with three layers of polyvinyl chloride (PVC) cling film and two layers of duct tape, while the other was not. The results showed that sealing the specimens during curing increased the compressive strength, and these increases were 18% for the reference mortar and 18% and 12%for mortars produced with 6 mm and 12 mm PVA fiber, respectively. Sealed curing enhanced fracture energy and peak loads and reduced the rate of capillary water absorption. With fiber inclusion, increases of up to 1508% in fracture energy values were achieved. The results revealed that sealing samples during curing significantly affects the mechanical properties.